SAR Image Classification And Field Measurement In Antarctica - Tan, Teik Eooi (2006)
This project proposes to interpret and classify the sea ice extent and land cover in the Antarctica. The aim of this thesis is to present the work done in the interpretation and classification of images using both active and optical microwave satellite imagery in Ross Island of Antarctica.